La désobéissance civile aux Etats-Unis contemporains : triomphe incomplet du libéralisme sur la gauche, routine et réactivation par les mouvements sociaux de l’immigration - Mathieu Bonzom (Amnis)
Civil disobedience occupies an important place in the history of protest and mobilization in the United States. For this very reason, its definition is unstable, often reshaped by transformations in the practices of participants and the rest of society. This article offers a number of points of reference to better situate civil disobedience in the contemporary United States on two levels. Firstly, civil disobedience will be situated in the political history of the United States in the light of the weakness of the left, and the preserved influence of a political tradition that the left has not managed to challenge once and for all: liberalism. Anchored in the liberal tradition, civil disobedience cannot, however, be reduced to it, and presents itself as a tactic that is the subject of multiple political struggles over its scope and meaning, demonstrating the incomplete triumph of liberalism over the left. Secondly, drawing on examples from the immigrant mobilizations of the 2000 and 2010 decades, with a counterpoint to the Civil Rights Movement of the 1950s and 60s, the article shows how the diversity of civil disobedience practices is structured by cyclical mutations, between routinization and defusing on the one hand, revival and reactivation on the other, where reactivation depends on the taking of certain forms of risk which is then turned against the authorities by drawing on mass mobilization.